Contemporary Behaviorisms in Debate - Zilio, Diego; Carrara, Kester [UNESP] (Springer Nature, 2021)
This book presents and discusses seven contemporary theoretical approaches to behavior analysis that build upon the foundations laid by B.F. Skinner's radical behaviorism and renew its legacy. These contemporary approaches show that behaviorism is not a monolithic or static intellectual tradition, but a dynamic movement, which changes and adapts in face of new questions, issues, and perspectives. The death of behaviorism has been proclaimed since its early days - a premature assessment, to say the least - but this volume shows that behaviorism is alive and kicking, even thirty years after its main proponent passed away. This volume contains seven sections, each one dedicated to a particular variation of contemporary behaviorism: Howard Rachlin's teleological behaviorism, William Baum's molar behaviorism and multiscale behavior analysis, John Staddon's theoretical behaviorism, John Donahoe's biological behaviorism, Gordon Foxall's intentional behaviorism, Steven Hayes' contextual behaviorism or contextual behavioral science, and Emilio Ribes-Iñesta's field-theory behaviorism. Each section contains three chapters: the first one written by the original proponent of each of these forms of behaviorism, the second one written by a commentator, and the third one written by the proponent, replying to the commentator. Contemporary Behaviorisms in Debate will be a valuable tool to behavior analysts and psychologists in general by providing an introduction to contemporary forms of behaviorism and promoting debates about the main philosophical issues faced by the field of behavior analysis today- issues that can directly influence future epistemological variations in the selection process of behaviorisms. By doing so the book is directed not only to the present, but, more importantly, toward the future of the field.
Keywords: Applied Behavior Analysis; Behavior Analysis; Behaviorism; Biological Behaviorism; Contextual Behaviorism; Intentional Behaviorism; Molar Behaviorism; Radical Behaviorism; Teleological Behaviorism; Theoretical Behaviorism